2019
DOI: 10.1136/vetreco-2018-000274
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of four giant Aldabra tortoises (Aldabrachelys gigantea)

Abstract: ObjectivesIn recent years echocardiography has become a good diagnostic tool in Zoo Medicine but in some cases, it is still a challenge. In Aldabra giant tortoise (Aldabrachelys gigantea) the big size of animals and the few individuals hosted in Zoo are critical points for the application of this diagnostic technique.The purposes of this research were: to evaluate the feasibility of the diagnostic imaging technique on big-sized turtles; to define the echographic parameters for this species; and to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Pericardial effusion has been suspected as both a pathologic and nonpathologic finding in previous studies of tortoises. 4,15,16 Based on this study and previous cases of heart diseases in tortoises, it is the opinion of the authors that a small amount of anechoic pericardial effusion is a physiologic finding in Galapagos and Aldabra tortoises.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Pericardial effusion has been suspected as both a pathologic and nonpathologic finding in previous studies of tortoises. 4,15,16 Based on this study and previous cases of heart diseases in tortoises, it is the opinion of the authors that a small amount of anechoic pericardial effusion is a physiologic finding in Galapagos and Aldabra tortoises.…”
Section: Discussionmentioning
confidence: 79%
“…The echocardiographic measurements collected in this study were similar to the four tortoises previously studied in similar age groups. 4 The information provided in this study can be used as a guide on how to perform echocardiograms in awake Galapagos or Aldabra tortoises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 In reptiles, pericardial effusion was initially considered an indicator of cardiac disease but is now increasingly documented as incidental in some species. 7,21,32,42 Ultrasound examination of reptiles and amphibians are frequently conducted under chemical or physical restraint. 2-4,6-8,13,21,27, 30,32,33,37,41,42 In this study, the ultrasonographic appearance of major coelomic organs was reported in conscious, unrestrained axolotls in ventral recumbency, thereby lessening the possible effects of stress, sedation, and physical compression of the coelomic organs.…”
Section: Discussionmentioning
confidence: 99%